Cabining Judicial Discretion Over Forensic Evidence with a New Special Relevance Rule - Shoucair, Emma F.E. (2018)
Modern forensic evidence suffers from a number of flaws, including insufficient scientific grounding, exaggerated testimony, lack of uniform best practices, and an inefficacious standard for admission that regularly allows judges to admit scientifically unsound evidence. This Note discusses these problems, lays out the current landscape of forensic science reform, and suggests the addition of a new special relevance rule to the Federal Rules of Evidence (and similar rules in state evidence codes). This proposed rule would cabin judicial discretion to admit non-DNA forensic evidence by barring prosecutorial introduction of such evidence in criminal trials absent a competing defense expert or a high showing of scientific viability